ANALISIS ANOMALI PASAR EFISIEN PADA RETURN SAHAM: Studi Kasus Perusahaan Sub Sektor Farmasi Yang Terdaftar Di BEI Periode 2016-2017 - Jefta Wijayadi, - (2019)
Efficient market anomaly is a deviation that occurs in the capital market which causes available information not to reflect stock prices. The research purposes (1) analyze and prove the day of the week effect on stock returns, (2) analyze and prove the month effect on stock returns, The research sample is daily stock data of pharmaceutical sub-sector companies for the period of 2016-2017 in the form of closing prices. Testing is done by multiple linear regression methods with dummy variable. Based on the results of the study (1) the day of the week effect occur in pharmaceutical sub-sector shares where Wednesday, Thursday and Friday partially affected the pharmaceutical sub-sector shares (2) the month effect occur in pharmaceutical sub-sector shares where April, July, and November partially influence.